Intrapancreatic accessory spleen in child - Yankov, Ivan; Boyanov, Nikola (The Turkish Journal of Pediatrics, 2022)
Background. Intrapancreatic accessory spleen is a congenital abnormality with duplicated splenic tissue located in ectopic sites. Case. We report a case of 10-year-old male patient with an infrequent finding of intrapancreatic mass. The examination of complete blood count, biochemistry, tumor markers were within the normal reference ranges. Imaging series found an intrapancreatic mass without wash-out effect on contrast-enhanced ultrasound, MRIintensity equal to splenic one and no increased glucose metabolism on PET/CT. Follow-up of the patient did not demonstrate progression of the size or change of ultrasound characteristics of the lesion. Conclusions. Intrapancreatic accessory spleen is an asymptomatic lesion and without the need of surgical therapy. It is important to differentiate it from pancreatic malignant tumors.
Keywords: CEUS; PET/CT; accessory spleen; contrast-enhanced ultrasound; pancreatic tumor